2015
DOI: 10.1513/annalsats.201412-600oc
|View full text |Cite|
|
Sign up to set email alerts
|

Latent Tuberculosis Infection Screening and 2-Year Outcome in Antiretroviral-Naive HIV-Infected Patients in a Low-Prevalence Country

Abstract: Systematic screening for latent TB infection by IFN-γ release assay identifies a population at high risk of active TB over the next months. An extensive diagnostic work-up for active TB must follow positive IFN-γ release assay, before considering treatment of latent infection. Clinical trial registered with www.clinicaltrials.gov (NCT00805272).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…There was no consistent association with the risk of LTBI for CD4 count, HIV viral load, or ART. Low CD4 count was not associated with an increased risk of LTBI among PLHIV, [10][11][12]17,22 and some studies (particularly those which used TSTs to diagnose LTBI) reported higher rates of LTBI in participants with high CD4 counts. 14,16,24,26 This is likely due to lower sensitivity of diagnostic tests for LTBI at lower CD4 counts, which is well documented for TSTs but less so for interferon-gamma release assays (IGRAs).…”
Section: Ltbimentioning
confidence: 82%
See 4 more Smart Citations
“…There was no consistent association with the risk of LTBI for CD4 count, HIV viral load, or ART. Low CD4 count was not associated with an increased risk of LTBI among PLHIV, [10][11][12]17,22 and some studies (particularly those which used TSTs to diagnose LTBI) reported higher rates of LTBI in participants with high CD4 counts. 14,16,24,26 This is likely due to lower sensitivity of diagnostic tests for LTBI at lower CD4 counts, which is well documented for TSTs but less so for interferon-gamma release assays (IGRAs).…”
Section: Ltbimentioning
confidence: 82%
“…Homelessness, and living or working in a collective group or institution, were associated with higher risks of LTBI, 10,13,18,19 Proximity to persons with TB was also important; close contact with a TB case increased the risk of LTBI 10,11,19,21,45 and active TB, 25,29,40 and a study set in a prison demonstrated that closer proximity was associated with increased risk. 25…”
Section: Other Social Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations